2019
DOI: 10.1007/s10967-019-06844-8
|View full text |Cite|
|
Sign up to set email alerts
|

Production of 47Sc with natural vanadium targets: results of the PASTA project

Abstract: The goal of PASTA project (acronym for production with accelerator of 47 Sc for theranostic applications) is the determination of excitation functions associated to several nuclear reactions, aimed at yielding the theranostic radionuclide 47 Sc. This work reports the main results obtained by irradiating natural vanadium targets with proton beams up to 70 MeV. Particular care is also given to the co-production of 46 Sc, the only isotopic contaminant with half-life longer than 47 Sc. Experimental results are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Experimental data on nat V can hence be interpreted in broad energy range as coming from a monoisotopic 51 V target and reaction cross-sections can be derived. The cross-sections of the nat V(p,x) 47 Sc nuclear reaction were measured up to 70 MeV proton beam (Jafari et al 2019;Pupillo et al 2019;Ditroi et al 2016), the low reaction yields are the disadvantage of this approach.…”
Section: Production Of 47 Sc Using Protonsmentioning
confidence: 99%
“…Experimental data on nat V can hence be interpreted in broad energy range as coming from a monoisotopic 51 V target and reaction cross-sections can be derived. The cross-sections of the nat V(p,x) 47 Sc nuclear reaction were measured up to 70 MeV proton beam (Jafari et al 2019;Pupillo et al 2019;Ditroi et al 2016), the low reaction yields are the disadvantage of this approach.…”
Section: Production Of 47 Sc Using Protonsmentioning
confidence: 99%
“…From the new results, it is concluded that protons of energy up to about 80 MeV are very suitable for the production of 67 Cu not only when isotopically enriched 68 Zn is used as target material [16,33] but also if enriched 70 Zn would be the target, provided good radionuclidic purity is achieved. For production of the β − -emitter 47 Sc (for review see [4]), neither the intermediate energy reaction 48 Ti(p,2p) 47 Sc investigated earlier nor the 51 V(p,αp) 47 Sc process studied recently [34] appears to be successful because of the high level of the radionuclidic impurity 46 Sc. With regard to the conversion electron emitter 117m Sn, the production route 116 Cd(α,3n) 117m Sn was established [11].…”
Section: Current Nuclear Data Activitiesmentioning
confidence: 99%
“…The nuclear reaction mechanisms relevant for radionuclide production at cyclotrons are dominated by compound nucleus formation and by pre-equilibrium emission and all the three codes are based on nuclear reaction models developed to describe these processes. A quick review of all the models used can be found in [22] and in the codes references.…”
Section: Nuclear Reaction Codesmentioning
confidence: 99%